Investigation of Binding Behavior between Drug Molecule 5‐Fluoracil and M4L4‐Type Tetrahedral Cages: Selectivity, Capture, and Release. Issue 15 (9th February 2017) - Xu, Wei‐Qin; Fan, Yan‐Zhong; Wang, Hai‐Ping; Teng, Jun; Li, Yu‐Hao; Chen, Cheng‐Xia; Fenske, Dieter; Jiang, Ji‐Jun; Su, Cheng‐Yong
Abstract: Two analogous M4 L4 ‐type tetrahedral cages (smaller: MOC‐19; larger: MOC‐22) were synthesized and investigated for their interactions with the anticancer drug 5‐fluoracil (5‐FU) by NMR spectroscopy, high‐resolution electrospray‐ionization mass spectrometry (HR‐ESI‐MS), and molecular simulation. The cage's size and window are of importance for the host–guest binding, and consequently the smaller MOC‐19 with a more suitable size of cavity window was found to have much stronger hydrogen‐bond interactions with 5‐FU. The porous nanoparticles of MOC‐19 exhibited outstanding behavior for the controlled release of 5‐FU in a simulated human body with liquid phosphate‐buffered saline solution. Abstract : Capture the drug : 5‐Fluorouracil (5‐FU) can be selectively captured by an M4 L4 metal–organic cage in both solution and crystalline state, and be released in a controlled way in phosphate‐buffered saline solution up to 60 % within 108 h, significantly retarding the burst release of 5‐FU. These binding‐behavior studies provide clues for the understanding of drug loading in the crystalline state.